2010
DOI: 10.1007/s00394-010-0140-9
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated fatty acids repress the expression of adipocyte fatty acid binding protein via the modulation of histone deacetylation in RAW 264.7 macrophages

Abstract: Unsaturated fatty acids inhibited the basal as well as LPS-induced A-FABP expression. The mechanism may involve histone deacetylation and anti-inflammatory effect of unsaturated fatty acids may be at least in part attributed to their repression of A-FABP expression in RAW 264.7 macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…This study revealed that mobilization of bioactive lipids from adipose tissue regulates systemic metabolic homeostasis. Other works have confirmed that increased palmitoleate production influences metabolism in the absence of FABP and through activation of SCD1 (65,66).…”
Section: Is Palmitoleate a Lipokine?mentioning
confidence: 80%
“…This study revealed that mobilization of bioactive lipids from adipose tissue regulates systemic metabolic homeostasis. Other works have confirmed that increased palmitoleate production influences metabolism in the absence of FABP and through activation of SCD1 (65,66).…”
Section: Is Palmitoleate a Lipokine?mentioning
confidence: 80%
“…Dendritic cells deficient in FABPs were poor producers of pro-inflammatory cytokines-interleukin-6 (IL-6) and TNF-α- and did not promote pro-inflammatory T-cell responses, suggesting that metabolic-inflammatory pathway cross-regulation by A-FABPs plays a significant role in adaptive immune responses and inflammation [10]. These results-coupled with the observations that unsaturated fatty acids, such as palmitoleic acid, oleic acid, linoleic acid, linolenic acid, and eicosapentaenoic acid, significantly repressed the basal as well as lipopolysaccharide-induced A-FABP expression in macrophages and depletion of A-FABP expression by RNA interference (RNAi) decreased cyclooxygenase 2 (COX-2) mRNA expression and potentiated the repression by linoleic acid [11] -give interesting insights into the relationship among A-FABP, cytokines, and unsaturated fatty acids and their involvement in sepsis and other critical illnesses.…”
Section: Adipose-fatty Acid-binding Protein and Inflammationmentioning
confidence: 97%
“…What is more, unsaturated fatty acids often counteract inflammatory pathways induced by saturated fatty acids; for example, in macrophages PUFAs suppress palmitic acid-induced increases in LOX1 and FABP expression [66;67]. Conjugated linoleic acid (CLA) has been shown to cause regression of preestablished murine atherosclerotic plaques, accompanied by a decrease in lesion macrophage accumulation and suppressed COX2, cPLA2, MCP1, and MMP9 expression in macrophages [68].…”
Section: Macrophage Phenotypic Polarization In Response To Anti-inflamentioning
confidence: 99%